Evaluation of the effectiveness of a corrective and rehabilitation program using gravity postisometric relaxation exercises, self-massage and myofascial release on the biogeometric profile of posture and cardiovascular system parameters of women of the second period of mature age - Kashuba, Vitalii; Ruban, Larysa; Efymenko, Pavlo; Honcharov, Oleksii; Kanishcheva, Oksana (Фізична реабілітація та рекреаційно-оздоровчі технології, 2025)
urpose. To scientifically substantiate, develop and experimentally verify the impact of a correctional and rehabilitation program using gravitational postisometric relaxation exercises, self-massage and myofascial release on the state of the biogeometric profile of posture and parameters of the cardiovascular system of women in the second period of adulthood. Material & Methods. The ‘School of Women's Health’ was organised. The total number of 79 people was women aged 36-45 years. The study involved two groups of women with complaints of chronic pain in the cervical spine and fluctuations in the parameters of the cardiovascular system: A group of women aged 36-40 years (n=16) and a group of women aged 41-45 years (n=15). Study procedure: heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured. Posture examination was performed in the frontal and sagittal planes using the REEDCO posture scale. Measurement of the depth of physiological cervical bend (cervical point) was performed according to the method of Z.P. Kovalkova. With correct posture, the depth of the cervical spine curve is within 5-5.5 cm. Statistical data processing was performed using the statistical package STATISTICA 13.0 (StatSoft). Results. A correctional and rehabilitation programme was developed for the subjects of the ‘School of Women's Health’, which consisted of three blocks: means of physical culture and sports rehabilitation, psychocorrection, and educational part. In the first block, it was proposed to perform isometric gymnastic exercises aimed at relaxing and strengthening the neck muscles; myofascial release using a massage roll. The aim of the educational component of the programme was to teach women how to perform self-massage of the neck on their own. The research and work on the correctional and rehabilitation programme lasted 3 months. The women spent 21 days in the School of Women's Health under the supervision of a rehabilitation specialist. Subsequently, the women worked independently under the programme, keeping in touch with the rehabilitation specialist through online communication in Viber, WhatsApp and Telegram messengers. During the initial communication, all the women complained of recurrent headaches, dizziness, palpitations, and high blood pressure. The results of the formative experiment showed a significant improvement in all parameters of the cardiovascular system (p˂0.05). After the implementation of the correctional and rehabilitation programme, the scores on the REEDCO posture scale statistically significantly increased in women aged 36-40 years by 1.04 times (p<0.05), in women aged 41-45 years by 1.12 times (p<0.05). The introduction of myofascial release into the correctional and rehabilitation programme in women of the second period of mature age had a positive effect on changes in the cervical spine: the depth of spinal curvature according to the method of Z.P. Kovalkova in women aged 36-40 years statistically significantly increased by 1.12 times (p<0.05), in women aged 41-45 years by 1.29 times (p<0.05) Conclusions. Training in the ‘School of Women's Health’ according to the developed correctional and rehabilitation programme had a positive effect on the parameters of the cardiovascular system, namely, normalisation of heart rate, blood pressure, and blood pressure. The use of gravitational post-isometric relaxation, self-massage of the cervical spine, myofascial release significantly improved the biogeometric profile according to the REEDCO posture scale, positively influenced the change in the depth of spinal curvature according to the method of Z.P. Kovalkova.